Time dependent contribution of char oxidation and flame heat feedback on the mass loss rate of timber. (March 2021) - Morrisset, David; Hadden, Rory M.; Bartlett, Alastair I.; Law, Angus; Emberley, Richard
Abstract: Experiments were conducted to quantify the magnitude and contribution of flame heat feedback and char oxidation on the burning of timber. Using both oxidative and inert environments (air and nitrogen) a methodology was developed to determine the individual contribution of flame and char oxidation. The rate of pyrolysis, expressed through the mass loss rate, was used to calculate the individual contributions of flame heat flux and char oxidation. The process of timber combustion was divided into an initial transient regime and quasi-steady regime. Equivalent heat flux contributions were calculated using the mass loss rate and the heat of pyrolysis. At the peak mass loss rate, the flame heat feedback contributed up to 60% of the total mass loss rate. The total contribution of flame radiation and char oxidation was determined to be constant with incident applied heat flux at quasi-steady state (2.5–2.9 kW/m 2 ). However, the contribution towards peak mass loss rate decreases at higher incident heat fluxes. Flame heat fluxes were calculated between 19.9 and 20.6 kW/m 2 at low external heat fluxes (20 and 25 kW/m 2 ). The resulting heat flux contributions agree with previous studies, with particularly good agreement at lower heat fluxes. Highlights: Experiments conducted in air and nitrogen to assess timber flammability. Timber mass loss rate behavior divided into a transient and quasi-steady regimes. Flame and char contribute to mass loss rate but the effect decreases at high heat flux. The total contribution of flame and oxidation is constant at quasi-steady state. Calculated flame heat flux values range from 20.3 ± 0.3 kW/m 2 at the peak.